PMMA-LiBOB gel electrolyte for lithium ion batteries - Kufian, M.Z.; Yusuf, S.N.F.; Majid, S.R.; Arof, Abdul Kariem (2010)
Different amounts of lithium bis(oxalate) borate (LiBOB) have been added into a mixture of equal amounts of ethylene carbonate (EC) and propylene carbonate (PC) by weight. The highest conducting liquid electrolyte is 0.6 M LiBOB in ECiPC with room temperature conductivity of 4.1 X 10'3 S cm'l. Different amounts of PMMA are then added to this composition and heated between 70-80 °C for 20 min to obtain gel polymer electrolytes. The sample containing 18,67 wt.% PMMA was chosen for characterization and fabrication of lithium ion battery. Transference number measurements for lithium ion from Bruce-Vincent and DC polarization methods are 0,26 and 0.22, respectively. Linear sweep voltammetry indicates that the gel electrolyte decomposition voltage is approximately 4,7 V. Cyclic voltammetry shows an anodic peak at 1.30 V, 1.31 V and 2.45 V vs Li at a scan rate of 1, 5 and 7.5 rnv s", respectively, indicating decomposition of LiBOB. Battery performance over 20 cycles shows discharge capacity of about 130 mAhg'l,